Discurso jurídico, mulher e ideologia: uma análise da “Lei Maria da Penha” - Gomes, Acir de Matos (2011)
Take as the corpus examined in this study called the "Maria da Penha Law" – Law nº. 11340 of August 7, 2006 – establishing mechanisms to curb and prevent domestic violence against women, provide for the creation of Courts and Domestic Violence against Women, and establishes measures to protect and assist women in situations of domestic violence. The law is a political act that represents the will of the people. Considering that all (men and women) are equal in accordance with article 5.º of the Constitution of Brazil, the choice of corpus is justified by considering how relevant is conceived institutional, legal discourse and the contemporary woman in our society : a fragile being that needs protection because of a chauvinistic position, still dominant today. The choice of theoretical framework of French Discourse Analysis is justified by the fact that she investigates the field of the statements in order to understand the events that made possible the establishment of discourse, and crystallization of certain meanings in our culture, and considering the unconscious, history and ideology. The senses, for not being clear, open space to the interpretation of what is not said and not are exhausted. The same statement can, in different conditions of production, producing various discursive effects. The overall goal of this research is to investigate the discursive and legislative history of Brazilian women and identify the ideological context of the emergence of the "Maria da Penha Law" which aims to curb domestic violence against women. As a specific objective which aims to examine the image, setting up institutional and legal discourse of women in contemporary society by being a law recently published in Brazil. The research is literature and analysis of qualitative and comparative data. We understand that the "Maria da Penha Law" reflects a sense, the contemporary tension between the social roles of the Brazilian woman: submissive woman and woman protagonist of great deeds. The results identify a position in favor of the frail woman / victimized, assuming an aggressor. They point to the existence of discourses that disrupt the discursive memory of family consisting of opposite sexes, the civil marriage and cohabitation.